Peran Strategi Pemasaran Digital dalam Meningkatkan Kesadaran Merek dan Loyalitas Konsumen: Studi Kasus Platform E-commerce di Indonesia - Yesawen, Yohannes; Ady, Sri Utami (Jurnal EMT KITA, 2026)
The aim of this article is to analyze the role of digital marketing strategies in enhancing brand awareness and consumer loyalty on e-commerce platforms in Indonesia. This article employs a qualitative literature review method by examining various references from leading international journals published in the last five years. The findings of the research indicate that digital marketing strategies, including content personalization, the use of social media, and consumer data, have a significant impact on improving brand awareness. Furthermore, brand awareness plays a crucial role as an important mediator between digital marketing strategies and consumer loyalty. The discussion reveals that consumer loyalty is influenced not only by brand awareness but also by adequate digital experiences and the quality of service provided by the platform. In conclusion, to enhance consumer loyalty, e-commerce platforms in Indonesia need to design comprehensive digital marketing strategies that focus not only on brand recognition but also on delivering consistent and satisfying user experiences.